1997
DOI: 10.1007/bf03011974
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cerebral metabolic and circulatory responses to nitrous oxide by 6-hydroxydopamine in dogs

Abstract: Purpose: To determine whether cerebral metabolic and circulatory consequences of N20 result from activation of the sympathoadrenal system. The effects of pretreatment with intradstemal injection of 6-OHDA, which produces chemical sympathectomy, were studied in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…29 Difference between the effects of postischemic xenon and postischemic nitrous oxide on tPA-induced brain hemorrhages and disruption of the blood-brain barrier are likely to occur at the vascular, rather than the parenchymal, level. This could be because xenon has no effect or even decreases cerebral blood flow in specific brain regions at concentrations to 1 minimum anesthetic concentration, [45][46][47] whereas in contrast, nitrous oxide at concentrations as low as 0.5 minimum anesthetic concentration is well known to increase cerebral blood flow and cerebral blood flow velocity, 48,49 conditions that could favor disruption of the blood-brain barrier, particularly during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…29 Difference between the effects of postischemic xenon and postischemic nitrous oxide on tPA-induced brain hemorrhages and disruption of the blood-brain barrier are likely to occur at the vascular, rather than the parenchymal, level. This could be because xenon has no effect or even decreases cerebral blood flow in specific brain regions at concentrations to 1 minimum anesthetic concentration, [45][46][47] whereas in contrast, nitrous oxide at concentrations as low as 0.5 minimum anesthetic concentration is well known to increase cerebral blood flow and cerebral blood flow velocity, 48,49 conditions that could favor disruption of the blood-brain barrier, particularly during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In children, nitrous oxide has been shown to increase Vmca during a balanced anesthetic technique (11) and causes cerebral excitation and an increase in CMRO 2 (14). Although the exact mechanism is not known, sympathoadrenal stimulation (20, 21), and mitochondrial activation (14, 22), have been postulated. Using contrast‐enhanced magnetic resonance perfusion measurements, Lorenz et al (23) demonstrated an increase in regional cerebral blood flow and volume with nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose utilization data were taken from the following sources for: mouse [65,66]; rat [67-73]; rabbit [74]; squirrel [75]; cat [76-80]; macaque monkey [81-84]; baboon [85]; goat [86]; sheep [87] (both glucose and oxygen); human [5,88-93]. Oxygen consumption data were taken from the following sources for: rat [94]; cat [95]; dog [96]; macaque monkey [97]; baboon [98]; human [5,99]. …”
Section: Supplementary Materialsmentioning
confidence: 99%